Protection against shigellosis caused by shigella dysenteriae serotype 4 in Guinea pigs using escherichia albertii dm104 as a live vaccine candidate strain - Chowdhury, Fatema Moni; Rahman, Mohammed Ziaur; Sarkar, Md Murshed Hasan; Rabbi, Fazle A.; Khan, Sirajulislam; Ahsan, Chowdhury Rafiqul; Birkeland, Nils Kåre (© 2017 Akadémiai Kiadó, 2018)
This article was published in the Acta Microbiologica et Immunologica Hungarica [© 2017 Akadémiai Kiadó, Budapest] and the definite version is available at : http://doi.org/10.1556/030.64.2017.015 The Journal's website is at: http://akademiai.com/doi/abs/10.1556/030.64.2017.015